MORFOLOGI PEMBUNGAAN DAN SISTEM REPRODUKSI MERBAU (Intsia bijuga) PADA PLOT POPULASI PERBANYAKAN DI PALIYAN, GUNUNGKIDUL - Liliana Baskorowati; Sugeng Pudjiono (Jurnal Pemuliaan Tanaman Hutan, 2015)
Information regarding the flowering morphology, as a first step to understand the reproductive system, is essential. The purpose of this study is to determine the flowering morphology and the reproductive systems of merbau. Observation of flowering and fruiting intensity was undertaken every week for 6 consecutive months, from May to November 2013. Observations of the development of generative organs were carried out on daily basis to determine the duration and the length of each development stage of flowers and fruits. Results showed that flowering of merbau is arranged in spikes, hermaprodite with un synchronous flowering between and within spikes. Reproductive organs are protandry and apparently heterostyly type, indicating that self-incompatibility may occur in this species. None fruit was formed from self-pollination experiment; supporting the allegation of crosspollination systems (xenogamy). Flowering occurs twice a year with peak flowering in June and November, followed by fruit maturation in the next 3 months. Various types of insect visitors found during this study, however very few insect can be determined as pollinators. Flowers and pollinator limitation lead to the mechanism of self-incompatibility causing low reproductive success on this species. Therefore, an artificial cross-pollination or an introduction of pollinators needs to be done in order to enhance the reproductive success of this species.